Long-term outcomes of visual motor integration and motor development children with retinopathy of prematurity - Kutlutürk Yıkılmaz, Seval; Çelik, Gökhan; Günay, Murat; Kızılay, Osman; Algün, Zeliha Candan (My University, 2024)
Premature infants have a risk of neurodevelopmental deficits. Little is known, however, about how retinopathy of prematurity (ROP) affects visual motor integration (VMI), which is necessary for both fine motor skills and further school abilities. Due to the systemic escape of bevacizumab in the treatment of ROP, concerns regarding the long-Term neurodevelopmental effect of the drug have arisen. The aim is to evaluate VMI and motor development long-Term outcomes after intravitreal bevacizumab (IVB) injection and laser treatment for ROP. Two groups of premature children were included: Bevacizumab group-16 premature children who received IVB treatment and laser group-23 premature children who underwent laser photocoagulation treatment in this single center cross-sectional study. At 2-6 years of age, VMI (Beery-Buktenica Developmental Test), motor development (Peabody Developmental Motor Scales-2), visual acuity, and refractive status were assessed. The incidence of abnormal visual function was significantly higher in bevacizumab group than in laser group (p = 0.022). The incidence of abnormal VMI skill was significantly higher in bevacizumab group than in laser group (p = 0.024). Incidences of abnormal gross, fine, and total motor skills were significantly higher in bevacizumab group compared to laser group (p < 0.05). Premature children who received bevacizumab for ROP demonstrated significantly lower VMI and motor development features than those with laser treatment at preschool age. Although our results suggest the relevance of bevacizumab injection in impaired VMI and motor development outcomes, general level of sickness rather than treatment might be the cause of delayed motor development.
Keywords: Intravitreal Bevacizumab; Laser; Motor Development; Neurodevelopmental Outcomes; Retinopathy of Prematurity; Visual Motor Integration